2018
DOI: 10.1093/cid/ciy179
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Sputum Culture Conversion in Tuberculosis–Human Immunodeficiency Virus–Coinfected Patients With Low Isoniazid and Rifampicin Concentrations

Abstract: Although low antituberculosis drug concentrations did not translate to a high proportion of patients with treatment failure, the association between low concentrations of rifampicin and isoniazid and delayed culture conversion may have implications for tuberculosis transmission. Clinical Trials Registration: NCT01782950.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 28 publications
1
39
1
Order By: Relevance
“…Several studies have recognized the role of underexposure of one or more compounds and the association of this event with unfavorable outcomes, such as slow response or treatment failure. In the same study population, Sekaggya‐Whiltshire and colleagues found a significant association between low concentrations of RIF and INH and delayed culture conversion and concluded that this may have implications for TB transmission. In this pharmacogenetic analysis, we observed that INH exposure (both as AUC 0–4 and C max ) could be predicted by gender and by genetic variants in three genes: NAT2 , SLCO1B1 , and PXR .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have recognized the role of underexposure of one or more compounds and the association of this event with unfavorable outcomes, such as slow response or treatment failure. In the same study population, Sekaggya‐Whiltshire and colleagues found a significant association between low concentrations of RIF and INH and delayed culture conversion and concluded that this may have implications for TB transmission. In this pharmacogenetic analysis, we observed that INH exposure (both as AUC 0–4 and C max ) could be predicted by gender and by genetic variants in three genes: NAT2 , SLCO1B1 , and PXR .…”
Section: Discussionmentioning
confidence: 99%
“…In this prospective observational study, the correlation of anti‐TB drug concentrations and clinical response in individuals infected with HIV with new pulmonary TB was investigated. The study was conducted at the Infectious Diseases Institute, Kampala, Uganda, a center of excellence in HIV care and treatment …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations